Clinical Outcomes of Transcatheter Aortic Valve Implantation for Native Aortic Valves in Patients with Low Coronary Heights - Kim, Hyeongsoo; Lee, Seung-Jun; Hong, Sung-Jin; Shim, Chi-Young; Ahn, Chul-Min; Kim, Jung-Sun; Kim, Byeong-Keuk; Hong, Geu-Ru; Ko, Young-Guk; Choi, Donghoon; Jang, Yangsoo; Hong, Myeong-Ki (Yonsei medical journal, 2021)
Acute coronary occlusion is a rare but fatal complication that may occur during trans-catheter aortic valve implantation (TAVI) and appears more frequently in patients with low coronary heights. We evaluated the feasibility of self-expanding valves in patients with low coronary heights undergoing TAVI. TAVI for native aortic valve stenosis was conducted in 276 consecutive patients between 2015 and 2019 at our institute. Using multi-detector computed tomography (MDCT), information on the aortic valve, coronary arteries, and vascular anatomy in 269 patients was analyzed. Patients with low coronary heights were defined as those with coronary heights of 10 mm or less during MDCT analysis. Among the 269 patients, 29 (10.8%) patients had coronary arteries with low heights. The mean coronary height was 8.9±1.2 mm in the left coronary artery. These patients with low coronary heights were treated with self-expandable (n=28) or balloon-expandable (n=1) valves. Prophylactic coronary protection with a guidewire, balloon, or stent prepositioned down at-risk coronary arteries was not pursued in all patients. No acute coronary occlusion occurred in any of these patients during TAVI. Five patients (17.9%) died during follow-up (average of 553.8 days), including four from non-cardiogenic causes and one from a cardiogenic (aggravation of heart failure) cause. A considerable number of patients with low coronary heights were observed among TAVI candidates in this study. Use of a self-expandable valve may be feasible for successful TAVI without acute coronary occlusion in patients with low coronary heights.